Anisotropic constant-roll \(k\)-inflation model - Nguyen, Hoang Duy; Pham, Manh Tuyen; Le, Duc Thien; Do, Quoc Tuan (Communications in Physics, 2022)
In this paper, we would like to figure out whether a {\it k}-inflation model admits the Bianchi type I metric as its inflationary solution under a constant-roll condition in the presence of the supergravity motivated coupling between scalar and vector fields, \(f^2(φ)F_{μ u}F^{μ u}\). As a result, some novel anisotropic inflationary solutions are shown to appear along with a power-law one in this scenario. Furthermore, these solutions are numerically confirmed to be attractive, in contrast to the prediction of the Hawking's cosmic no-hair conjecture.